Sequential Injection Chromatography as Alternative Procedure for the Determination of Some Food Preservatives - Jangbai W. (2014)
Sequential injection chromatography for the determination of benzoic acid (BA), sorbic acid (SOA), and salicylic acid (SA) has been investigated. Separation was performed on a monolithic C-18, (5 × 4.6 mm) column which is normally used as a guard column, with 1% acetonitrile: ammonium acetate buffer pH 4.5 as a mobile phase at a flow rate of 1.20 mL/min at ambient temperature and with the UV detection at 235 nm. Under the conditions, separation of the three compounds was achieved within less than 3 min. Linear calibrations were found to be 1-100 mg/L for the three: BA, SOA, and SA with detection limits of 1.9, 0.7, and 0.3 mg/L. The developed procedure was demonstrated to be an effective alternative fast and simple method for the analysis of food, fruit juice, syrup, and soft drink samples. © 2011 Springer Science+Business Media, LLC.